Penanganan Stres Terkait Pekerjaan - Mulyono, Fransisca (Jurnal Administrasi Bisnis, 2010)
Work-related stress has become common phenomenon. Many considers it as an isolatedproblem, whereas this stress causes the performance of the company decreases.Managing this stress is still not done enough yet, even in the big companies in developedcountries, due to the low awareness among the managers regarding the problem.Individual worker suffers the stress, so she/he should handle her/his problem, indeed.But the role of the leaders is crucial to handle the problem, such as creating a conduciveand open environment. The last but not the least, the just and good treatmentof the leaders towards her/his subordinate reflects the good leadership.Keywords: work-related stress, the causes of stress, coping strategy